(untitled) (Educação e Pesquisa, 2022)
The Federal University of Alfenas (Unifal-MG) joined the Support Program for Restructuring and Expansion Plans of Federal Universities (Reuni) and the reservation of vacancies. It is now necessary to know the impact of these adhesions. Thus, the general objective of the research was to know the effects of the implementation of public policies at Unifal-MG regarding its democratizing goals of expansion and diversification of access. For this, these specific objectives were sought: measuring expansion; qualifying the students; knowing its distribution by the courses; describing the dynamics of dropout; and highlighting the role played by institutional configurations that drive expansion and regulate access to courses. The participants of the 2013 cohort of on-site graduation from their main campuses were investigated, using quantitative methods. It was observed that its students expanded and diversified, but this diversity was limited to certain careers. Dropout rates increased, affecting mainly new students, and institutional configurations led to internal segmentation. It is concluded that democratization policies reproduce inequalities because they are accompanied by mechanisms that dispose the recently included public in less attractive vacancies. The institutional configurations that carried expansion out and regulate access contributed to the promotion of a “backward quota policy” and dispensable access, giving freshmen a situation similar to the one they already have. Inclusive policies, combined with conformations that ratify selection and elimination processes operated by the education system prior to the university, preserve an elitist teaching model. Educational differences become socioeconomic inequalities, and the system is legitimized under the myth of democratization. Thus, the reproduction is approved.